Petroleum spill bioremediation by an indigenous constructed bacterial consortium in marine environments - Liu, Suxiang; Sun, Rui; Cai, Mengmeng; Kong, Yue; Gao, Yu; Zhang, Tonghuan; Xiao, Xinfeng; Qiao, Yanlu; Xue, Jianliang; Huang, Guofu (Ecotoxicology and environmental safety, 2022)
In the process of marine oil spill remediation, adding highly efficient oil degrading microorganisms can effectively promote oil degradation. However, in practice, the effect is far less than expected due to the inadaptability of microorganisms to the environment and their disadvantage in the competition with indigenous bacteria for nutrients. In this article, four strains of oil degrading bacteria were isolated from seawater in Jiaozhou Bay, China, where a crude oil pipeline explosion occurred seven years ago. Results of high-throughput sequencing, diesel degradation tests and surface activity tests indicated that Peseudomonas aeruginosa ZS1 was a highly efficient petroleum degrading bacterium with the ability to produce surface active substances. A diesel oil-degrading bacterial consortium (named SA) was constructed by ZS1 and another oil degrading bacteria by diesel degradation test. Degradation products analysis indicated that SA has a good ability to degrade short chain alkanes, especially n-alkanes (C10-C18). Community structure analysis showed that OTUs of Alcanivorax, Peseudomona, Ruegeria, Pseudophaeobacter, Hyphomonas and Thalassospira on genus level increased after the oil spill and remained stable throughout the recovery period. Most of these enriched microorganisms were related to known alkane and hydrocarbon degraders by the previous study. However, it is the first time to report that Pseudophaeobacter was enriched by using diesel as the sole carbon source. The results also indicated that ZS1 may have a dominant position in competition with indigenous bacteria. Oil pollution has an obvious selective effect on marine microorganisms. Although the oil degradation was promoted after SA injection, the recovery of microbial community structure took a longer time. •An indigenous petroleum degrading bacterium and biosurfactant producer Peseudomona aeruginosa ZS1 was isolated.•An efficient oil-degrading bacterial consortium (SA) was constructed.•Peseudomona aeruginosa ZS1 has an advantageous position in the bioremediation process.•First time to report that Pseudophaeobacter was enriched by using diesel as the sole carbon source.•A promising in situ strategy for marine oil pollution bio-treatment was proposed.